Analysis of the impact of space organization on the viability of the Karaj metropolitan core - behrouz hashemi; farzaneh sasanpor; ali movahed; Habiallah Fasihi (تحقیقات کاربردی علوم جغرافیایی)
Abstract With the rapid growth of population and urbanization since the last century, the complexity and understanding of the spatial organization of the city, as well as the ability to predict urban events in its spaces, have become difficult and in some cases impossible. Karaj metropolis is one of the major metropolitan areas of Iran that has been experiencing rapid population growth and this has led to complexity of space and consequently to complexity of organization recognition and analysis and its spatial structure and impact of livelihood components. It has become a spatial system. The main purpose of the present study is to identify the role and impact of Karaj's spatial organization on its nuclear viability. The research method is quantitative and descriptive-exploratory. The study area was Karaj metropolis and its main nuclei. The statistical population of this study is citizens living in the sub-nucleus of Karaj. The sample size was 378persons. The data used in this study were collected through library and field research. Data were analyzed using spatial statistics, spatial arrangement, and T-test and Friedman test. The results show that the Karaj metropolitan organization and spatial structure are interconnected and connected to some of the major routes, forming sub-nuclei away from the core and thus transferring the functional and service applications from the center to be the peripheral nucleus. This has affected the viability of the core. Decrease in biodiversity has occurred in different physical, social, economic and environmental dimensions that have affected the environmental and economic aspects less than the other two dimensions, so it can be concluded that the Karaj Spatial Organization has an impact on its viability.